Multiresolution view-dependent splat based volume rendering of large irregular data - Meredith, J.; Kwan-Liu Ma (IEEE Parallel and Large Data Visualization and Graphics Symposium 2001, 2001)
We present techniques for multiresolution approximation and hardware-assisted splat based rendering to achieve interactive volume visualization of large irregular data sets. We examine two methods of generating multiple resolutions of irregular volumetric grids and a data structure supporting the splatting approach for volume rendering. These techniques are implemented in combination with a view-dependent error based resolution selection to maintain accuracy at both low and high zoom levels. In addition, the error tolerance may be adjusted at run time to obtain the desired balance between high frame rates and accurate rendering. Along with an effective way to compute gradients for lighting, we offer an integrated solution for interactive volume rendering of irregular-mesh or meshless data, and we demonstrate our technique on unstructured-grid data sets from aerodynamic flow simulations.